Clinically applicable antibiotic modification of ready-to-use calcium phosphate cement pastes - Alicia Zeiner; Johannes K. Konrad; Sandra Hinderer; Andreas Hoess; Sascha Heinemann; Uwe Gbureck (Journal of Orthopaedic Surgery and Research)
Abstract Background Ready-to-use non-aqueous cement pastes consist of an organic, water-miscible liquid phase in which cement powder is dispersed. While the modification of classical aqueous powder/liquid cement pastes with antibiotics has been extensively investigated, only a few studies previously published aimed at drug modification of premixed cement pastes. Methods A simple method for modifying such ready-to-use pastes with the model antibiotic vancomycin is described. It was demonstrated that mixing the cement paste and vancomycin solution multiple times using an adapter between two syringes resulted in macroscopically homogeneous pastes. The antibiotic-loaded cements were thoroughly characterized with regard to their physicochemical properties and their drug release profile. Results Drug modification with vancomycin had no adverse effects on cement properties in terms of mechanical performance, phase composition, porosity and pore size distribution. Drug release from ready-to-use pastes exhibited a lower initial burst release of 14.5% compared to 47.9% for aqueous powder/liquid cement pastes after 24 h. At later time points, the initial exponential release kinetics slowed down due to both a decreased concentration gradient and structural changes of the cement matrix during setting. This resulted in sustained release of the antibiotic for more than 30 days. The released vancomycin maintained high antimicrobial activity against S. aureus with inhibition zones of 5.4–6.8 mm in an agar diffusion test. Conclusion The results demonstrated that modification of ready-to-use cement pastes with vancomycin is a potential candidate for clinical application, as it preserves both the material’s properties and the antibiotic’s activity.